COSTS AND CHALLENGES: AYUSHMAN BHARAT (AB-PMJAY) SCHEME IN ASSAM'S URBAN AND RURAL SETTINGS - Yadav, Anil Kumar; Bora, Bhaskarjyoti (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Modicare or National Health Protection Scheme (NHPS), a healthcare initiative launched by Prime Minister Narendra Modi has sparked global interest and excitement in the sector. Although 500 million Indians are expected to receive health insurance under this specific healthcare policy, the negative aspects of Modicare far exceed any potential advantages in terms of achieving universal access to high-quality healthcare. This paper ascertains the healthcare expenditure of the households and evaluate the challenges faced by them in financing healthcare expenditure through PM-JAY or Ayushman Bharat schemes in Kamrup Metro and Kamrup districts of Assam representing both urban and rural settings. The study found that the healthcare costs is more in the Urban areas as compared to the rural one. Furthermore, it concludes that the scheme (PM-JAY) provides essential healthcare coverage, but there are significant disparities in healthcare costs and challenges faced by beneficiaries in both urban and rural settings.